Children's needs, types and costs of placements and their stability : comparisons using the Cost Calculator for Children's Services - Jean Soper; Lisa Holmes (2008)
Background and introduction: The Cost Calculator for Children's Services is a computer model formulated within a research programme. The initial study, on the costs and consequences of placing children in care or accommodation, formed part of a national research initiative funded by the Department of Health (and later the Department for Education and Skills) at a time when concerns were being expressed about spiralling costs, different agencies measuring these costs in different ways and pressures on limited resources. The model has now been developed, piloted and made available as a software application for use by social care agencies wishing to gain a better understanding of costs and their relationship to outcomes when children are placed in care or accommodation. It offers a variety of reports that allow users to carry out many different analyses.